Teachers’ training in Marche Region (IT): ICT and continuing professional development - Ceccacci, Laura (Form@re - Open Journal per la formazione in rete, 2018)
Indire’s empirical research regarding digital skills of Italian teachers involved in the National Operational Programme 2007-2013 “Skills for Development” (European Social Fund, ESF), published in 2016, highlighted the existence of a positive link between the number of courses on the use of technologies in teaching and teachers’ training needs. This article presents the results of a quantitative survey that the Regional School Office of Marche carried out at the end of the first year of the implementation of the National Plan for Teachers’ Training 2016-2019. It confirms the high attractiveness of the training paths on digital skills despite the wide range of courses available at regional level. It seems they can endorse positive link between demand and supply in the perspective of lifelong learning. I percorsi di valorizzazione professionale dei docenti nelle Marche: le TIC e la formazione continua La ricerca pubblicata nel 2016 da Indire sulle competenze digitali del personale docente coinvolto nel Programma Operativo Nazionale (PON) 2007-2013 “Competenze per lo sviluppo” (Fondo Sociale Europeo, FSE) aveva messo in luce l’esistenza di una correlazione positiva fra la numerosità dei corsi sull’uso delle tecnologie nella didattica e l’espressione dei fabbisogni formativi in questo ambito. L’intervento presenta i risultati di un monitoraggio di tipo quantitativo condotto dall’Ufficio Scolastico Regionale (USR) Marche sul territorio regionale alla conclusione del primo anno di realizzazione del Piano nazionale per la formazione dei docenti 2016-2019, che confermano il mantenimento di un alto grado di attrattività dei percorsi dedicati al digitale a fronte di un’ampia offerta proposta a livello territoriale. Essi sembrano quindi avere la capacità di attivare circuiti virtuosi, in cui l’offerta alimenta la domanda nell’ottica del lifelong learning e dell’apprendimento permanente.